KESALAHAN SISTEMATIS PENGGUNAAN SKALA LIKERT DALAM PENELITIAN: ANALISIS SYSTEMATIC LITERATURE REVIEW - Antoro, Budi (Jurnal Multidisiplin Sosial dan Humaniora, 2025)
The Likert scale is the most widely used measurement instrument in social science and educational research, but its use often involves systematic errors that threaten research validity. This study aims to identify and analyze systematic errors in the use of Likert scales and develop an advanced methodological solution framework based on comprehensive systematic literature review. The method used is a Systematic Literature Review (SLR) of 22 articles from various theoretical perspectives (statistical, psychometric, and methodological) published between 1932-2022. The analysis results identified five categories of fundamental errors: (1) conceptual and terminological errors, (2) instrument design errors, (3) statistical analysis errors, (4) methodological errors, and (5) reporting and interpretation errors. This research develops a three-tier solution hierarchy ranging from Rasch IRT Model and MCMC Algorithm (Tier 1), Assignment of Scores and Successive Intervals (Tier 2), to 11-point Likert scales and conversion tables (Tier 3). Critical findings show that the Likert scale controversy is not a pure statistical problem, but rather a methodological education problem and evidence-based solution implementation. The developed decision framework provides practical guidance for selecting ordinal-interval conversion methods based on data characteristics, distributional assumptions, and research objectives.